A feasibility investigation of speciation by Fe K-edge XANES using a laboratory X-ray absorption spectrometer - Mottram,L.M.; Cafferkey,S.; Mason,A.R.; Oulton,T.; Kuan Sun,S.; Bailey,D.J.; Stennett,M.C.; Hyatt,N.C. (Journal of Geosciences, 2020)
We demonstrate effective speciation of Fe in model compounds from analysis of the weak pre-edge features in Fe K-edge XANES spectra, with a commercially available laboratory X-ray spectrometer, using a spherically bent crystal analyser and a low power X-ray tube, in Rowland circle geometry. Direct comparison with XANES data acquired from a third generation synchrotron bending magnet beamline, using the same specimens, validated quantitative agreement in determination of the total integrated intensity and centroid position of the pre-edge feature, which are a probe of the electronic configuration and symmetry of the absorber atom, and hence oxidation state and co-ordination number. This work opens the door to rapid and routine speciation studies of Fe by laboratory XANES, even for materials with relatively dilute absorber concentration of only a few mol. %.